Assessment of polyglycolic acid scaffolds for periodontal ligament regeneration - Yun Wu; Haibin Xia; Bi Zhang; Yan Zhao; Yining Wang (Biotechnology & Biotechnological Equipment, 2018)
Periodontal tissue engineering is a possible strategy for regeneration of human periodontal ligaments (PDLs) around dental implants. The aim of this study was to investigate the feasibility of three-dimensional polyglycolic acid (PGA) fibre mesh as a scaffold for human PDL cells in periodontal tissue engineering with a nude mouse model. Human PDL cells at a density of 2 × 107/mL were seeded onto porous PGA scaffolds. After seven days of incubation in vitro, the PGA–cell constructs and cell-free scaffolds were subcutaneously implanted on the back of BALB/c-nu mice bilaterally. The mice were sacrificed in batches at 2, 4, 6 and 8 weeks after implantation, and the harvests were examined histologically. In our study, PGA scaffolds promoted mRNA expression of collagen type I, collagen type III and fibronectin in PDL cells. Masson's trichrome staining showed that after two weeks, the implants were well vascularised in vivo. Fluorescence microscopy indicated that the newly formed tissues were derived from the GFP-labelled human PDL cells. Our study suggested that the delivery of PDL cells via a non-woven PGA mesh might serve as a viable approach to promote periodontal tissue regeneration.